Strategi Kompetisi Antara Tokopedia Dan Shopee Menggunakan Teori Permainan - Defrisa Yoga Putra; Defri Ahmad (Journal of Mathematics UNP, 2021)
TEMASEK is a company from Singapore. Based on research initiated by TEMASEKand Google  in  2015,internet  users  in  Indonesia  reached  92  million.  18  million  of  them  are  e-commerce connoisseurs and it is predicted that by 2025 there will be 119 million onIineshoppers in Indonesia. This increase will push the e-commerce market value to reach 81billionin 2025. This has resulted in many  e-commerce  popping  up  in  Indonesia,  the  top  two  being  Tokopedia  and  Shopee.  Therefore, managers are required to determine what strategies will hook consumers. Game theory is used to find the optimaIstrategy  for each pIayer.The  purpose  of study  is to find the optimaIvaIue  of the  game.This   study   uses   5   marketing   strategies,   namely   promotion/advertising,   completeness,   service, payment, and price. The population in this study is Mathematics Students from January to June 2021, the  sample  of  this  research  is  Mathematics  students  at  Padang  State  University  who  have  used Tokopedia  and  Shopee.There  are  two  methods  of  solving,  namely  using  a  pure  strategy  or  a  mixed strategy.In  this  case,  the  settlement  uses  a  pure  strategy  and  theoptimaI  vaIue  of  the  game  is  0,04 where Tokopedia comes out as the winner with a maximum profit that will be obtained which is 4% if using  a  price  strategy,  while  Shopee  will  minimize  losses  with  its  strategy,  namely  a  more  diverse payment strategy